Managing the whole landscape: historical, hybrid, and novel ecosystems. Issue 10 (1st December 2014) - Hobbs, Richard J; Higgs, Eric; Hall, Carol M; Bridgewater, Peter; Chapin, F Stuart; Ellis, Erle C; Ewel, John J; Hallett, Lauren M; Harris, James; Hulvey, Kristen B; Jackson, Stephen T; Kennedy, Patricia L; et al.
Abstract : The reality confronting ecosystem managers today is one of heterogeneous, rapidly transforming landscapes, particularly in the areas more affected by urban and agricultural development. A landscape management framework that incorporates all systems, across the spectrum of degrees of alteration, provides a fuller set of options for how and when to intervene, uses limited resources more effectively, and increases the chances of achieving management goals. That many ecosystems have departed so substantially from their historical trajectory that they defy conventional restoration is not in dispute. Acknowledging novel ecosystems need not constitute a threat to existing policy and management approaches. Rather, the development of an integrated approach to management interventions can provide options that are in tune with the current reality of rapid ecosystem change.